Pre-Questioning Technique Towards Students Reading Comprehension - Effrina Yuricki (Universitas Nurul Huda, 2021)
The aim of this research is to know the influence of the Pre-Questioning technique towards students’ reading comprehension. In this research, the writer used the experimental method or known as descriptive quantitative research. The population was 103 students in three classes. The sample was taken by using Cluster Random Sampling Technique. The writer took two classes as the sample of research namely experimental and control class, it consisted of 73 students. The main technique in measuring students’ reading comprehension was multiple choices which consisted of 40 items. Each item has five options; A, B, C, D, and E. The score for each item was 2,5. In calculating the data analysis, the writer used the t_test formula. Based on the data analysis by using the t_test formula, the writer got the result that H_a is accepted. It was obtained that t_test =4.07, t_table for α = 0.05 is 1.67 and for α = 0.01 is 2.39. Therefore, the conclusion is there was an influence of Pre-Questioning towards students’ reading comprehension of the tenth grade at SMK Budi Utomo Way Jepara in 2020/2021. Based on the result of the research, it is clear that the Pre-Questioning technique can improve students’ reading comprehension.